Regulating Force in Putting by Using the Borg CR100 scale® - Molander, Bo; Olsson, CJ; Stenling, Andreas; Borg, Elisabet (Frontiers in Psychology, 2013)
Studies investigating the regulation of force of motor actions are scarce, and particularly so in the area of sports. This is surprising, considering that in most sports precise force is of great importance. The current study demonstrates how a psychophysical scale, the Borg CR100 scale® (Borg & Borg, 2001), can be used to assess subjective force as well as regulate force in putting. Psychophysical functions were calculated on the relationships between judgments of force using the CR100 scale and the length of putting shots, examined in a laboratory setting, where 44 amateur golfers played on both flat and uphill surfaces. High agreement and consistency between CR 100 ratings and distances putted was demonstrated. No significant differences in handling the scale were observed between younger (mean age ≈37 years) and older (mean age ≈69 years) players or between players of different skill level. This study provides a new innovative use of an existing instrument, the Borg CR 100 scale ®, in order to understand the regulation of force needed for putts of various lengths and surfaces. These results and the potential future benefits of the psychophysical approach in golf are discussed.